Studi Kasus Penatalaksanaan Skabies Pada Anak Laki-Laki Usia 12 Tahun Melalui Pendekatan Kedokteran Keluarga Di Wilayah Kerja Puskesmas Tanah Pasir - Intan Zuryani; Noviana Zara (Pusat Riset dan Inovasi Nasional, 2024)
Patient An MM was brought by his parents to the Tanah Pasir Community Health Center Children's Polyclinic with complaints of itching on both hands for the last 3 weeks. The initial complaint was that it felt like itching accompanied by the appearance of reddish spots, and over time, pimples appeared between the fingers. Complaints felt worse in the last week until the patient felt itchy all day and complaints of itching felt worse at night until the patient had difficulty getting to sleep because he kept scratching the part of the body that felt itchy. Based on the anamnesis of complaints obtained after contact with the patient's older brother who experienced similar complaints. A physical examination was carried out and the examination results were within normal limits. Primary data was obtained through anamnesis and physical examination by conducting home visits, filling in family folders, and filling in patient files. The assessment is carried out based on a holistic diagnosis at the beginning, process and end of the visit quantitatively and qualitatively. The interventions carried out include education about the causes of scabies in the family, education on environmental sanitation and cleanliness and management of the disease as well as explaining complications that may arise from the patient's disease so that the patient's family maintains better personal hygiene and environmental cleanliness.